Improvement of the separation evolution law and separation position determination method of mining overburden strata - Da, Yuxin; Ning, Zhiyuan; Huang, Zilong; Du, Qirui; Liu, Qi; Zhao, Jinhai; Li, Qinghai (Frontiers in Earth Science, 2023)
In view of the shortcomings of the traditional method of determining the position of the separation layer, according to the actual movement of the pressure balance arch and the rock layer in the overburden, the concept of the triangular separation domain is proposed, and the relationship between the range of the triangular separation domain and the mining distance and the mining fracture angle is established. The calculation method of rock load is modified. By analyzing the stress mode in the pressure arch of the separation zone, the mechanical model of the deflection calculation of each rock stratum is established. Combining the triangular separation zone with the new mechanical model, the calculation model of the dynamic evolution analysis of the separation zone and the calculation model of the composite beam in the separation zone are established. The traditional method and the improved method are used to determine the separation position in an actual mining example. The field exploration proves that the results of the improved method described in this paper are more accurate. The model predicts the position of overburden separation by comparing the deflection between adjacent strata on the same horizontal contact surface, and can accurately predict the position of separation above the working face.